Pengembangan Media Pembelajaran Berbasis Alur Merdeka - Ujang Jamaludin; Reksa Adya Pribadi; Gitta Zahara (Peneliti.net, 2023)
Learning media is a tool that can provide assistance to teachers in teaching and learning activities and play a role in conveying messages to students, with the aim of improving student learning outcomes and achieving better educational goals. Based on Merdeka Flow, the whole learning process is represented through the Merdeka cycle. The method applied in this study is a literature review approach. That learning media has an important role as a learning resource for students, which assists them in obtaining the messages and information conveyed by the teacher. Selection of the right type of learning media depends on the context of learning and student characteristics, as well as the learning objectives to be achieved. Teachers can choose learning media according to the needs and characteristics of students and support the learning process effectively. with Merdeka Flow provides a systematic and holistic guide in facilitating effective learning, enabling students to think, collaborate, and apply knowledge in meaningful ways.